Effects of a natural extract of Aronia Melanocarpa berry on endothelial cell nitric oxide production - Varela, Claudia Elena (J Food Biochem, 2015)
The effects of acute and chronic treatment with Aronia extracts on NO production and endothelial nitric oxide synthase (eNOS) phosphorylation in bovine coronary artery endothelial cells were investigated. Acute time-course and concentration-response experiments were performed to determine the time and concentration at which Aronia induced maximal NO synthesis and eNOS phosphorylation. The findings indicate that relatively low concentrations (0.1 μg/mL) of Aronia extract significantly induced NO synthesis and eNOS phosphorylation after 10 min of treatment. Increased sensitivity of eNOS and a significant increase in NO synthesis resulted from longer-term stimulation with Aronia (48 hr) and an acute re-treatment of the cells (10 min). PRACTICAL APPLICATIONS: These in vitro results may be translated into potential future clinical applications where Aronia extracts may be used for prevention and coadjuvant treatment of cardiovascular diseases via increases in endothelial NO synthesis and related improvements in vascular functions. Given the dose-response effect of Aronia extract in vitro and metabolism of polyphenols that occurs in humans, dose-response studies would be necessary to define the optimal daily amount to be consumed.